Different bioavailability of phenanthrene to two bacterial species and effects of trehalose lipids on the bioavailability. Issue 3 (23rd February 2020) - Chang, Jae-Soo; Cha, Daniel K.; Radosevich, Mark; Jin, Yan
Abstract: Effects of trehalose lipids produced from Rhodococcus erythropolis ATCC 4277 on phenanthrene (PHE) mineralization by two soil microorganisms were investigated. Biodegradation experiments were conducted, with and without the biosurfactant, in three batch systems: water, soil, and soil–water slurry. PHE sorption to the soil did not limit the mineralization by the test microorganisms, Pseudomonas strain R (PR) and Sphingomonas sp. strain P5-2 (SP5-2). Both microorganisms, however, demonstrated significant difference in the PHE mineralization capability in the systems. While SP5-2 mineralized PHE faster than PR in liquid culture, PR having more hydrophobic surface greatly exceeded SP5-2 in ability to access soil-sorbed PHE. While the addition of the biosurfactant little affected the apparent cell hydrophobicity of SP5-2, it substantially improved PHE mineralization by this strain in all systems tested. Contrary to SP5-2, the apparent cell hydrophobicity was significantly stimulated with increasing concentration of the biosurfactant for PR. However, the biosurfactant had no significant effect on PHE mineralization by this microorganism. The results demonstrated that the addition of the biosurfactant may have great potential for remediation of sites contaminated with polycyclic aromatic hydrocarbons but its effects and benefits may be dependent on characteristics of microorganisms involved and environmental conditions.